"I do not sing for the love of singing": The roots of Latin American leftist art in London. (7th February 2019) - Cruz Mosquera, Carlos
Abstract : Art in Latin American has often been used to stand up against capitalism, imperialism, and the white supremacist structures that have been imposed on the region since the colonial era. Frida Kahlo, Oswaldo Guayasamin, Gabriel Garcia Marquez, Victor Jara, Violeta Parra, Ali Primera, Silvio Rodriguez, Mercedes Sosa, Mario Benedetti, and Pablo Neruda have all used their art as a weapon to expose centuries of social, political, and economic injustices committed against the exploited masses. This revolutionary tradition has greatly influenced Latin American artists in the diaspora. While their presence often goes under the radar in the United Kingdom, this article will demonstrate that there is a long‐established tradition of leftist artists who do not simply replicate the work of the aforementioned Latin American giants but who also create art that speaks to the specific struggles of Latin American immigrants in the United Kingdom.